The Historical Figure of Omar al-Mukhtar and Islamic Martyrdom in Indonesia - Dhont, Frank (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2012)
The story of Omar al-Mukhtar resisting Italian colonisation of Libya had great potential as a rallying point for anti-colonial sentiment in the Indies stirred up by Islamic politicians under a Pan-Islamic banner. The Dutch colonial government was quite aware of the issueâs sensitivity. It forbade newspapers and Islamic leaders from even mentioning the story of Omar al-Mukhtar with the result that the proposed boycotts against Italy could not become widespread. The effectivity of Dutch policy snuffed out the possibility of the figure of Omar al-Mukhtar becoming a rallying point for those politically active in the struggle against colonialism. Those that would become Indonesian National Heroes with Islamic roots were in fact figures re-cast in a national, secular mould. After ndonesian independence it was national, local identity which dominated over that of Islamic martyrdom.[Kisah perjuangan Omar al-Mukhtar dalam melawan kolonialisasi Italia menjadi kisah yang menginspirasi gerakan anti-kolonialisme di Hindia-Belanda yang dimotori oleh kalangan politisi muslim melalui semboyan Pan-Islamisme. Pemerintah kolonial Belanda merespon dengan hati-hati isu sensitif ini dengan melarang koran dan pemimpin Muslim menceritakan kisah perjuangan Omar al-Mukhtar. Namun, pelarangan ini tidak cukup berhasil. Omar al-Mukhtar menjadi inspirator gerakan anti-kolonialisme. Mereka yang disebut sebagai pahlawan nasional dengan latar belakang muslim sebenarnya tokoh-tokoh yang dihadirkan dengan nuansa nasional/sekuler. Setelah Indonesia merdeka, identitas lokal-nasional itulah yang kemudian lebih dominan ketimbang identitas keislaman.]